CONTINUOUS CASCADE OF KPI SYSTEM FROM STRATEGY TO PRACTICE IN THE BUILDING MATERIALS INDUSTRY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article presents a methodology for building a KPI system in construction materials enterprises from strategy to practice through continuous cascade. The approach is combined with the” goal–indicator–target–initiative “chain, the” CPI passport", a unified dictionary and the MDM/ETL-based information discipline.he article presents a methodology for building a KPI system in construction materials enterprises from strategy to practice through continuous cascade. The approach is combined with the” goal–indicator–target–initiative “chain, the” CPI passport", a unified dictionary and the MDM/ETL-based information discipline. Go-Live effects are evaluated using ITS/DiD, variance decomposition, process mining, and SPC; ERP/CRM/MES integration keeps the indicator–driver–process triad close to real-time. As a result, increases OTD and Plan adhesion, decreases DIO of Backorder; The council / committee hierarchy increases the speed of decisions, while quarterly review guarantees continuous improvement. The proposed solution will ensure effective resource utilization, transparency and sustainable competitiveness.